Using continuous student feedback to course-correct during COVID-19 for a nonmajors chemistry course - Hwang, Candy S. (Journal of Chemical Education, 2020)
The two major impetuses to improve STEM education are the shift to online learning and increasing active learning and engagement. Although the COVID-19 pandemic necessitated a rapid shift to online learning, this shift came at the cost of losing on-ground active learning strategies. This study provides descriptive analytical information on the impact of COVID-19 as it relates to student engagement, attendance, and viewership of video-recorded lectures for a nonmajors chemistry course. After the shift online, lecture video views significantly increased and weekly attendance significantly decreased. Prior to the pandemic, on-ground engagement via an active learning activity (i.e., Plickers) was significantly associated with on-ground achievement (i.e., exam 1). However, no significant association was found between online engagement (i.e., written responses/feedback submitted via a learning management system, referred to as LMS student feedback) and online achievement (i.e., final exam), potentially because the engagement resembled a formative assessment more than an active learning activity. Nonetheless, there was tremendous value in soliciting LMS student feedback for directing the course. Throughout the online period, there was an average of 112 responses per assignment, for a total of 1,344 responses, representing roughly a third of the students. Finally, analyses revealed no significant association of on-ground and online engagement, which suggests a different subset of students engaged while on-ground vs online. Instructors should highly consider soliciting weekly feedback through low-stakes assignments to gauge student learning and improve their courses while online. Copyright © 2020 American Chemical Society and Division of Chemical Education, Inc.
11 citations (Crossref) [2023-10-31] tex.ids: hwangUsingContinuousStudent2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85091001155 type: Article
Keywords: Distance Learning/Self Instruction; First-Year Undergraduate/General; Internet Web-Based Learning; Nonmajor Courses; dept.che; peer-reviewed